Threatening dystopias : the global politics of climate change adaptation in Bangladesh - Paprocki, Kasia (Cornell series on land., 2021)
"The political ecology of climate change adaptation is shaped by longer histories of development and agrarian change. In coastal Bangladesh, competing visions of this history and of desirable development trajectories under climate change among practitioners, scientists, and local residents shape different possibilities for the future"--